PD-1/PD-L Pathway Potentially Involved in ITP Immunopathogenesis - Nie, Mu; Liu, Yang; Li, Xiu-xiu; Min, Ya-nan; Yang, Dan-dan; Li, Qiang; Feng, Qi; Hou, Yu; Li, Guo-sheng; Sun, Jian-zhi; Hou, Ming; Shi, Yan (Thrombosis and Haemostasis, 2019)
The binding of programmed death 1 (PD-1) to its ligands PD-L1 and PD-L2 on antigen-presenting cells turns off autoreactive T cells and induces peripheral tolerance. Aberrant PD-1/PD-L signalling could result in a breakdown of peripheral tolerance and lead to autoimmune diseases. In this study, we detected PD-1 and PD-L expression on T cells and dendritic cells (DCs) in immune thrombocytopenia (ITP) patients with active disease by flow cytometry. The effects of PD-L1-Fc fusion protein (PD-L1-Fc) on T cells and on secretion of interferon-γ (IFN-γ) and interleukin-2 (IL-2) were detected by flow cytometry and enzyme-linked immunosorbent assay, respectively. Compared with healthy controls, PD-1 expression was significantly increased in CD4+ T cells and CD8+ T cells from patients with active ITP. However, PD-L1 expression on monocyte-derived DCs was lower in patients with active ITP than in healthy controls. In vitro assays revealed that PD-L1-Fc increased T cell apoptosis, inhibited activation and proliferation of CD4+ T cells and CD8+ T cells and decreased IFN-γ and IL-2 secretion in patients with active ITP. These results suggest that the aberrant PD-1/PD-L negative co-stimulatory pathway may play a role in ITP. Enhancing PD-1/PD-L signalling might be a promising therapeutic approach for ITP patients by enhancing T cell apoptosis, inhibiting T cell activation and proliferation and reducing secretion of inflammatory factors.
Keywords: immune thrombocytopenia; PD-1; PD-L1; PD-L2; T cell